Implementation of Teaching Derivational and Inflectional Morphemes to SMP Al Islah Surabaya - Savira Zaniar; Nailul Authar; Novi Rahmania Aquariza; Jauharotur Rihlah; Niken Ayu Pramudita (CV. Publikasi Indonesia, 2024)
This study investigates the integration of instructing derivational and inflectional morphemes at SMP Al Islah Surabaya to improve students' comprehension and its application to the English language. It aims to enhance students' vocabulary acquisition, reading comprehension, and writing skills by employing an effective curriculum and specific instructional methodologies. The present study employs a mixed-methods methodology, integrating quantitative language proficiency evaluations with qualitative observations of classroom interactions and student remarks. Initial results suggest that providing direct guidance on derivational and inflectional morphemes substantially impacts students' linguistic proficiency and apply grammatical principles with greater effectiveness. It emphasizes the significance of including morphology education in the language learning curriculum. It offers practical suggestions for teachers to cultivate a more profound morphology awareness among SMP Al Islah students and improve English language competency.